2017
DOI: 10.5558/tfc2017-021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate on juvenile mortality and Armillaria root disease in lodgepole pine

Abstract: Variable and sometimes high levels of mortality in lodgepole pine (Pinus contorta Dougl. ex Loud. var. latifolia Engelm.) planted in western Alberta have raised awareness of the need to forecast and ameliorate risks to reforestation success. Mortality and health of regeneration during the 12 years following harvest were monitored and evaluated in relation to climate, site and silvicultural treatments. Results suggest that physiological stress related to evapotranspiration is the most prevalent cause of overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Trees suffering physiological drought stress can be impaired in their ability to effectively produce such defences (Kolb et al 2016) recording period mirroring region-wide summer droughts (NOAA 2003(NOAA , 2007. Dempster (2017) remarked that incidence of A. ostoyae and mortality of juvenile lodgepole pine were related to increases in potential evapotranspiration with the proportion of infected trees corresponding to higher summer heat-moisture index values in addition to other climate variables. Morrison (2011) noted peaks in mortality of infected trees immediately following drought years but did not investigate any potential relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Trees suffering physiological drought stress can be impaired in their ability to effectively produce such defences (Kolb et al 2016) recording period mirroring region-wide summer droughts (NOAA 2003(NOAA , 2007. Dempster (2017) remarked that incidence of A. ostoyae and mortality of juvenile lodgepole pine were related to increases in potential evapotranspiration with the proportion of infected trees corresponding to higher summer heat-moisture index values in addition to other climate variables. Morrison (2011) noted peaks in mortality of infected trees immediately following drought years but did not investigate any potential relationship.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Armillaria ssp., one of the most destructive pathogens in European forests, CC is also expected to increase their activity and modify the growth of rhizomorphs, which increases the susceptibility of trees to these pathogens. In this case, a warmer and drier climate will be more beneficial for it [188,191,192]. As with insects, the migration of pathogens toward new regions with suitable climate conditions can contribute to increased forest damage.…”
Section: Disturbances and Extremes-climate Plaguesmentioning
confidence: 99%
“…They found that such thinning intensity significantly improved radial growth recovery after drought events, but it scarcely affected the resistance to drought-induced mortality. In the case of >40% basal area removal, if the crown size is allowed to increase in the case of a single heavy thinning intervention or because of very late and light multiple thinnings, then the initial positive effects on drought can even be reversed as the stand matures [42,142,143]. In the forestry context of Alberta, removing more than 40% of a stand's basal area during treatment is not recommended because of increased blowdown risk.…”
Section: Drought Resistancementioning
confidence: 99%